Automobile Insurance: Road Safety, New Drivers, Risks, Insurance Fraud and Regulation - Dionne, Georges; Laberge-Nadeau, Claire (Huebner International Series on Risk, Insurance and Economic Security, 1999)
Motor vehicle accidents are still a leading cause of death, even if the trend has somewhat declined over the past 20 years. Indeed, motor vehicle accidents are a significant cause of death in comparison with air and space transport accidents, homicides and even HIV infections, causes which are more often highlighted in the media. As shown in this book, motor vehicle accidents are particularly damaging to very young drivers. The assessment of driving risks is a common concern for road transportation safety and the automobile insurance industry. In both cases, there is an awareness of the great losses resulting from the deaths, injuries and property damage caused by traffic accidents. Research is essential to counteract this public health threat, to assess the success or failure of countermeasures, and to solve the problems it generates in the insurance industry. This book is for people concerned about road crashes (prevention and compensation) and about the insurance problems they pose - namely private and public institutional authorities, consultants, administrators, practitioners, and researchers interested in sharing the authors' experience in this domain. The book presents original contributions related to motor vehicle insurance and road safety. All papers have been evaluated by external referees. Four subjects are covered: 1) Automobile Insurance Pricing, Risks and Asymmetric Information; 2) Insurance Fraud; 3) Young Drivers: Licensing Policies, Evaluation and Risks; and 4) Road Insurance Regulation